Breaking the cycle: Reforming pesticide regulation to protect pollinators - Fisher, Adrian; Tadei, Rafaela [UNESP]; Berenbaum, May; Nieh, James; Siviter, Harry; Crall, James; Glass, Jordan R; Muth, Felicity; Liao, Ling-Hsiu; Traynor, Kirsten; Desjardins, Nicole; Nocelli, Roberta; et al. (Oxford University Press (OUP), 2023)
Over decades, pesticide regulations have cycled between approval and implementation, followed by the discovery of negative effects on nontarget organisms that result in new regulations, pesticides, and harmful effects. This relentless pattern undermines the capacity to protect the environment from pesticide hazards and frustrates end users that need pest management tools. Wild pollinating insects are in decline, and managed pollinators such as honey bees are experiencing excessive losses, which threatens sustainable food security and ecosystem function. An increasing number of studies demonstrate the negative effects of field-realistic exposure to pesticides on pollinator health and fitness, which contribute to pollinator declines. Current pesticide approval processes, although they are superior to past practices, clearly continue to fail to protect pollinator health. In the present article, we provide a conceptual framework to reform cyclical pesticide approval processes and better protect pollinators.
Keywords: pesticides; policy; pollinators; regulation; sustainability